2007
DOI: 10.1111/j.1462-5822.2006.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile salts induce expression of the afimbrial LDA adhesin of atypical enteropathogenic Escherichia coli

Abstract: SummaryAtypical enteropathogenic Escherichia coli (aEPEC) strains are frequently implicated in infant diarrhoea in developing countries. Not much is known about the adherence properties of aEPEC; however, it has been shown that these strains can adhere to tissuecultured cells. A chromosomal region designated the locus for diffuse adherence (LDA) confers aEPEC strain 22 the ability to adhere to culture cells. LDA is an afimbrial adhesin that contains a major subunit, LdaG, whose expression is induced on MacConk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…It was found that in response to bile E. coli is able to actively pump out bile salts through the efflux system AcrAB, thus limiting the toxic action of these compounds (Thanassi et al, 1997). In the diarrheagenic strains of E. coli, enteropathogenic E. coli (EPEC) and atypical enteropathogenic E. coli (aEPEC) bile salt stress resulted in an increase in adhesion of bacteria to human epithelial cells (de Jesus et al, 2005;Torres et al, 2007). Microarray analysis of STEC 0157:H7 indicated that the presence of bile salts resulted in protective alterations of the outer membrane, downregulating the expression of OmpF porin, through which bile pass into the periplasm of E. coli, and upregulating the efflux pump AcrA-AcrB, thereby limiting the toxic effects on the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that in response to bile E. coli is able to actively pump out bile salts through the efflux system AcrAB, thus limiting the toxic action of these compounds (Thanassi et al, 1997). In the diarrheagenic strains of E. coli, enteropathogenic E. coli (EPEC) and atypical enteropathogenic E. coli (aEPEC) bile salt stress resulted in an increase in adhesion of bacteria to human epithelial cells (de Jesus et al, 2005;Torres et al, 2007). Microarray analysis of STEC 0157:H7 indicated that the presence of bile salts resulted in protective alterations of the outer membrane, downregulating the expression of OmpF porin, through which bile pass into the periplasm of E. coli, and upregulating the efflux pump AcrA-AcrB, thereby limiting the toxic effects on the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Protein heat extraction is a procedure that has been used to identify some CFs in ETEC strains and other adhesins in pathogenic E. coli strains under different environmental conditions (21,34). We used this approach to obtain proteins from ETEC 1766a cultured at 20°C and 37°C, which were then separated by SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…These signals include factors that facilitate gastrointestinal adherence of the bacteria to the small intestinal or colonic epithelial cells (17,19). Studies investigating bile responses in E. coli include both commensals and diarrheagenic pathovars, including enteropathogenic E. coli (EPEC), enterotoxigenic E. coli (ETEC), and enterohemorrhagic E. coli (EHEC) (20)(21)(22)(23)(24)(25)(26)(27)(28). …”
Section: Escherichia Colimentioning
confidence: 99%